PENGARUH MANAJEMEN TEMPAT WISATA SEBELUM DAN SESUDAH DIKELOLA PEMERINTAH TERHADAP PENERIMAAN RETRIBUSI DI KABUPATEN MAGETAN - EVIANA WIJAYANTI, ELLY Eviana (Jurnal Akuntansi AKUNESA, 2014)
Related to the management of the first sights that are managed privately transferred to Local Government. Magetan must make and have bylaws to regulate it. Which ultimately determined Regency Regulation No. 13 of 2005 Magetan About Levy Recreation and Sports and the revised No. 2 of 2012 on Business service levies. Basically with the transfer of management rights of private parties to the local governments can levy receipts and PAD region itself. With the methods and forms of proper socialization and true to create an understanding of the substance and the provisions stipulated in the System Acceptance Levy. Keyworks: management of tourist attractions, Levy Proceeds